1990
DOI: 10.1007/bf03350695
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of testosterone and estradiol: a source of bias in comparative studies on breast cancer

Abstract: In this paper we present a study of the diurnal variation of testosterone (T) and estradiol (E2) in women, carried out as part of the design of a prospective study on the hormonal and nutritional etiology of breast cancer. Blood samples were obtained 5 times on the same day, in the morning and early afternoon, from 23 women aged between 25 and 63 yr. Twelve were sampled within the first days following daylight-saving time (SUMTI) introduction. In postmenopause, T mean values decreased from 08:00 h to 15:00 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…We adjusted for year of blood draw to account for any possible degradation in the analytes over time and adjusted for hour of the blood draw to adjust for possible diurnal variation, particularly of the androgens. 33 We were unable to document how the volunteers who gave blood for the breast cancer marker study, carried out in the 1970s and 1980s, differed from those who did not because no information was collected from those who did not participate; however, it is likely that any selection factors were similar for all study subjects included in this analysis. We also excluded some women who met the eligibility criteria for our study, but did not have serum or slides available.…”
Section: Discussionmentioning
confidence: 99%
“…We adjusted for year of blood draw to account for any possible degradation in the analytes over time and adjusted for hour of the blood draw to adjust for possible diurnal variation, particularly of the androgens. 33 We were unable to document how the volunteers who gave blood for the breast cancer marker study, carried out in the 1970s and 1980s, differed from those who did not because no information was collected from those who did not participate; however, it is likely that any selection factors were similar for all study subjects included in this analysis. We also excluded some women who met the eligibility criteria for our study, but did not have serum or slides available.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study like previous studies used only a single blood sample for the determination of estradiol levels. It has been reported that time of day has little effects on estradiol concentrations in postmenopausal women (Panico et al, 1990), however there seems to be an influence of lifestyle variables (Cauley et al, 1989) and a relatively low stability of the measurement over time (Cauley et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…From the present findings it may be inferred that the SCN is capable of monitoring the circadian, menstrual and circannual rhythms of circulating levels of sex hormones in humans from early puberty onwards until late adulthood [70, 71, 72, 73, 74, 75]. …”
Section: Discussionmentioning
confidence: 99%